Anmeldelser - Høgel, Sten (Danish Yearbook of Musicology, 2000)
Review of: Marie-Christine Skuncke & Anna Ivarsdotter: Svenska operans födelse. Studier i gustaviansk musikdramatik. Atlantis, Stockholm 1998.